Student perception of the implementation of a didactic guide for the teaching of the Dewey Decimal Classification System at the School of Library and Information Science of the University of Costa Rica (2022-2024) - Hernández-Arroyo, Wilson (2026)
This article analyzes the implementation of a didactic guide designed to support the learning of the Dewey Decimal Classification System (DCDS) in the Classification course of the School of Library and Information Science of the University of Costa Rica. The study arose from the need to strengthen the teaching-learning processes in complex technical contents such as document classification. The main objective was to evaluate the pedagogical effectiveness of the guide, from the students' perception. The approach was mixed, with a descriptive design. The quantitative phase consisted of a survey applied to 36 students enrolled in the second cycle 2024, while the qualitative phase was based on two retrospective focus groups with participants of cycles 2022 and 2023. Data was collected on structure, clarity, usefulness, design, learning styles and practical application. The results show a high appreciation of the resource: 83.4 % felt that the guide allowed for progressive and organized learning; 75 % highlighted the clarity of the instructions, and 80.5 % rated the practical exercises positively. However, areas for improvement were noted, such as the inclusion of more complex examples and interactive resources. It is concluded that the guide represents an effective and transferable resource to the professional context, although its adaptability to different learning styles should be strengthened. The study shows the potential of open teaching materials in library education.